Permanently online and permanently procrastinating? The mediating role of Internet use for the effects of trait procrastination on psychological health and well-being - Reinecke, Leonard; Meier, Adrian; Aufenanger, Stefan; Beutel, Manfred E.; Dreier, Michael; Quiring, Oliver; Stark, Birgit; Woelfling, Klaus; Mueller, Kai W. (New Media & Society, 2018)
A growing number of studies suggest that Internet users frequently utilize online media as “tools for procrastination.” This study thus investigated the relationship between trait procrastination, Internet use, and psychological well-being in a representative sample of N = 1,577 German Internet users. The results revealed that trait procrastination was associated with an increased use of leisure-related online content and impaired control over Internet use. As a result, Internet users high in trait procrastination showed a higher risk of experiencing negative consequence of Internet use in other life domains. These negative repercussions of insufficiently self-regulated Internet use partially accounted for the correlation between trait procrastination and impaired well-being (i.e. stress, anxiety, and depression). These findings underline the role of online media as an instrument for dysfunctional task delay among Internet users. Implications of the results are discussed with regard to media use and self-control in general and procrastinatory media use in specific.
CRIS-Team Scopus Importer:2021-02-02
Keywords: Habit; Internet use; procrastination; self-control; well-being